A Computer-Based System for Evaluation of Slub Yarn Characteristics. (9th January 2014) - Abd El-khalek, R.; El-Bealy, R.; El-Deeb, A.
Abstract : This research aims to build a computer-based system for measuring slub yarn characteristics and evaluating the results using statistical methods. The measuring system was based on the electrical condenser of the Uster evenness tester as a measuring sensor. A digital storage oscilloscope was used to convert the analogue output signals into digital data to be recorded on a computer. A designed computer program was constructed using MatLab language for signal analysis based on a proposed method. Final results from this system contained graphical plots for the three measured slub yarn geometrical parameters slub length, slub distance, and slub thickness and a final report for all the measured slub yarn characteristics. The results of tested slub yarn samples showed that actual slub geometrical parameters differ from nominal values and the difference had two level: prevailing difference and outlier values. Outliers which are considered slub yarn defects were detected and counted in a final report using the box plot statistical method which could be an effective industrial tool for evaluation of both yarn quality and machine performance. The prevailing difference was assessed using histogram comparison which could help in adjusting the setting of slub yarn device to obtain the required appearance.